SUPERVISION OF THE DEPARTMENT OF TRANSPORTATION IN PARKING MANAGEMENT AT THE NATIONAL UNITY PARK (TKB) MANADO CITY - ZULFIKAR, MOH. ZULFIKAR LASANDANGMOH; LENGKONG, FLORENCE DAICY; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this research is to know the supervision of the Department of Transportation in ParkingManagement in at the National Unity Park (TKB) Manado City in terms of supervision in the management ofparking framework of efforts to increase comfort of the community in the management of parking, supervisionitself based on Regulation No. 3 of 2011 Manado City Transportation Agency as the authorized and responsibleparty to arrange and manage parking. This research uses descriptive method of qualitative approach, and datacollection technique done by observation, interview technique and documentation. Number of informants asmany as 9 people. In this research, we use supervision process theory according to Situmorang and Juhir inSiagian 2008 which is the supervisory process approach includes 2 indicators as follows (1) direct control,covering (a) direct inspection, (b) on the spot observation, (c) on the spot report , (2) indirect control, including(a) oral reports, (b) written reports. The result of the research shows that the supervision of the TransportationAgency in Parking Management at the National Unity Park (TKB) of Manado City is not yet maximal or not yetgood, it can be seen in direct monitoring either direct inspection, on-site observation, on-site report according tofield observation according to informant officers not often conduct direct monitoring, which officers onlyroutinely do billing retribution’s parking every day.Keywords: Supervision Dapertement of transportasi, in Parking Management